Parenting in the Age of Preimplantation Gene Editing - Klipstein, Sigal (The Hastings Center report, 2017)
Medical science at its core aims to preserve health and eliminate disease, but a common theme in scientific discovery is the application of findings in ways that were not the primary intent. The development of diagnostic modalities to predict the health of resulting children has been a fundamental aim underpinning research into prenatal and preimplantation diagnostic modalities; however, the knowledge gained has in some cases been utilized for nonmedical purposes. As an example, amniocentesis developed to determine whether the pregnancy is chromosomally normal also provides information about the sex of the fetus, which normally does not affect health. The emerging gene-editing technologies that could be used to repair mutated disease-causing genes in an embryo will presumably also be able to be used to alter traits unrelated to disease. And yet, I will argue, the desire to preserve the mystery of reproduction remains a central value in humans’ quest to reproduce. This yearning to maintain the mysteries will likely temper the development of strategies to alter our genome and affect the genetic identities of our offspring. In my experience as an obstetrician and reproductive endocrinology and infertility subspecialist, people want to have, not the best possible baby, but rather their own baby.